Pet sematary [videorecording (Blu-Ray)] - King, Stephen, 1947-; Midkiff, Dale, 1959-; Gwynne, Fred; Crosby, Denise; Greenquist, Brad, 1959-; Lombard, Michael, 1934-; King, Stephen, 1947- (Paramount Home Entertainment, 2019)
A patch of woods is discovered to rejuvenate the dead and a new doctor in town uses it to restore the life of his dead son. But it soon becomes clear that his son has changed.